ANALISA KEBUTUHAN PENGGUNAAN LISTRIK BERDASARKAN AKTIVITAS PENGHUNI RUMAH TYPE 90 M2 - Imran, Mohammad; Gaib , Sri Janiansi; Detuage, Rahmat (Universitas Bina Taruna Gorontalo, 2024)
This study aims to analyze the need for electricity use in type 90 houses based on the activities of the occupants of the house. This increasingly sophisticated and versatile era, makes the use of electricity in the household a necessity for every user, which means that electricity has an important function in everyday life, especially in households. The more electricity use, the more Watt meters are needed. This study uses a field observation research method. The results of this study found that the maximum electricity usage of 798 Watt occurred at 18.00 and the minimum electricity usage of 140 Watt occurred at 13.00-14.00, so it can be concluded that the power used was 900 Watt. The use of electricity in this home case study is casuistic (depending on the level of electricity use, unless there is a power outage).